2015
DOI: 10.7860/jcdr/2015/14681.6692
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Treated Water and Dialysate in Haemodialysis Unit of A Tertiary Care Hospital

Abstract: Regular and continual monitoring of the disinfection protocol of the water distribution system in haemodialysis unit is necessary to get good microbiological quality of treated water and dialysate fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Therefore, the presence of all these bacterial varieties with resistant strains in treated water is a matter of concern in HD centers and should be taken seriously when assessing HD water quality by performing routine monthly disinfections with high-level disinfectants. Other solutions to improve the quality of HD water were recommended: disinfecting machines frequently by updating the disinfection protocol (Asserraji et al 2014;Verma 2015), biofilm analysis on tubing dialysis machines (Marion-Ferey et al 2003), improving nursing education on dialysis water (Chamney & James 2008), and conducting monthly quality assurance for risk analysis to the progress of water quality. The choice of piping materials is also essential.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of all these bacterial varieties with resistant strains in treated water is a matter of concern in HD centers and should be taken seriously when assessing HD water quality by performing routine monthly disinfections with high-level disinfectants. Other solutions to improve the quality of HD water were recommended: disinfecting machines frequently by updating the disinfection protocol (Asserraji et al 2014;Verma 2015), biofilm analysis on tubing dialysis machines (Marion-Ferey et al 2003), improving nursing education on dialysis water (Chamney & James 2008), and conducting monthly quality assurance for risk analysis to the progress of water quality. The choice of piping materials is also essential.…”
Section: Discussionmentioning
confidence: 99%
“…In one study on the bacteriological quality of treated water and dialysis in hemodialysis unit of a tertiary care hospital in 2015, it showed that thirty-six samples of treated water and 394 samples of dialysate analyzed for bacteriological contamination. 4 out of 36 (11.1%) samples of treated water and 44 out of 394 dialysate samples (11.2%) showed unacceptable bacteriological growth [15]. Totaro et al 2017 in Italy, from nine-dialysis water plants at nephrology wards within the city examined for identify microbial and chemical hazards.…”
Section: Maximum Allowable Level Microbiological Contaminantsmentioning
confidence: 99%
“…The bacteria enter the bloodstream through the oral cavity or other gates e.g. through lines and dialysates of hemodialysis, migrate to different places and damage the endothelium [37]. They weaken the intima of vessels, proliferate, create their biological colony, and build the plaque.…”
Section: Classical and New Mechanisms 0f Atherosclerosismentioning
confidence: 99%